2016
DOI: 10.1039/c6nr00476h
|View full text |Cite
|
Sign up to set email alerts
|

Engineering incremental resistive switching in TaOxbased memristors for brain-inspired computing

Abstract: Brain-inspired neuromorphic computing is expected to revolutionize the architecture of conventional digital computers and lead to a new generation of powerful computing paradigms, where memristors with analog resistive switching are considered to be potential solutions for synapses. Here we propose and demonstrate a novel approach to engineering the analog switching linearity in TaOx based memristors, that is, by homogenizing the filament growth/dissolution rate via the introduction of an ion diffusion limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
212
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(218 citation statements)
references
References 46 publications
5
212
0
1
Order By: Relevance
“…Multi-level resistive switching operation of five resistance states using different materials in ITO/RGO/ITO 15 and TiN/Ta 2 O 5 /Pt 16 structures have been demonstrated. Several research groups have reported multi-level switching operation with multiple states for brain-inspired neuromorphic applications 17, 18 . However there is no report on tunable multi-level resistive switching characteristics of the BaTiO x switching material in Cr/BaTiO x /TiN structure and its transport mechanism in each level is not reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-level resistive switching operation of five resistance states using different materials in ITO/RGO/ITO 15 and TiN/Ta 2 O 5 /Pt 16 structures have been demonstrated. Several research groups have reported multi-level switching operation with multiple states for brain-inspired neuromorphic applications 17, 18 . However there is no report on tunable multi-level resistive switching characteristics of the BaTiO x switching material in Cr/BaTiO x /TiN structure and its transport mechanism in each level is not reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…The diffuse process with time meets ~e −t/τ , as schematically illustrated in Fig. 4g 13 . However, it was different to fit the current decay curves with respect to time perfectly as e -t/τ at all time scale.…”
Section: Resultsmentioning
confidence: 96%
“…During the SET process, the device is programmed at self-compliance mode with a stop voltage of +0.8 V ( Figure S17a, Supporting Information). Wang et al have shown 27 conduction states in the TiN/SiO 2 /TaO x /Pt structure [51] and 15 conduction states in the Al/CuPc/LiF/ITO structure [18] at the SET condition. Afterward, the device is allowed to partially RESET at a stop voltage of −0.6 V ( Figure S17b, Supporting Information).…”
Section: Figure 2amentioning
confidence: 99%